2011
DOI: 10.1192/bjp.bp.111.095141
|View full text |Cite
|
Sign up to set email alerts
|

Aggression and seclusion on acute psychiatric wards: effect of short-term risk assessment

Abstract: Routine application of structured risk assessment measures might help reduce incidents of aggression and use of restraint and seclusion in psychiatric wards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
96
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 26 publications
(31 reference statements)
5
96
2
3
Order By: Relevance
“…Increasing the use of structured short-term risk assessment tools to evaluate risks associated with aggression and seclusion has been successful in reducing patient hours in seclusion (van de Sande et al, 2011), and may be particularly relevant for tailoring strategies to high-risk cases. Our research suggests that such tools should include information about previous seclusion/restraint episodes and hours in containment.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the use of structured short-term risk assessment tools to evaluate risks associated with aggression and seclusion has been successful in reducing patient hours in seclusion (van de Sande et al, 2011), and may be particularly relevant for tailoring strategies to high-risk cases. Our research suggests that such tools should include information about previous seclusion/restraint episodes and hours in containment.…”
Section: Discussionmentioning
confidence: 99%
“…An exception is the use of daily risk assessment instruments by nurses. Two cluster randomized studies showed that risk assessment reduced the number of aggressive incidents (49, 50) as well as the duration of seclusion (50). Only few hospitals, however, use these methods.…”
Section: Training/preventionmentioning
confidence: 99%
“…Information needed to rate the HCR-20-C is routinely collected in the course of admitting patients to a psychiatric inpatient unit, and prompting trainees to rate this structured measure could aid them in attending to valid risk markers from among the vast amount of information that may become available during the course of an admission workup. Third, the improvements in accuracy offered by use of a structured risk assessment tool have the potential to guide development of interventions to prevent violence (40). …”
Section: Discussionmentioning
confidence: 99%